Serum Immunoglobulins and complement subfactors levels in sodium valproate treated epileptic patients - Nazar A-K Hami; Mohammed Khalid Al-Nori; Omer AH Ahmed; Imad Abdul-Jabbar Thanoon (University of Mosul, 2011)
Objectives: To assess, the serum levels of immunoglobulins (IgG, IgA, IgM) and complement subfactors (C٣, C٤) in newly diagnosed epileptic patients in the pretherapy stage and ٣ months after valproate therapy, in comparison with controls. Methods: This study was conducted at Iben-Seena Hospital and the College of Medicine- University of Mosul from January to December ٢٠٠٩. Forty-two newly diagnosed epileptic patients were selected and included in this study. Fifty apparently healthy subjects , age and sex matched to the patients group also included and taken as a control. Initially from both the patients and controls, blood samples were taken and assessment of sera levels of immunoglobulins and complement subfactors were done by single radial immuno diffusion method, using commercial kits. Then patients were put on valporate therapy for ٣ months and a blood sample were taken from the patients and assay of the same parameters mentioned above were done using the same technique and the same kits. Results: There were insignificant differences between patients in pre-therapy stage and controls with regard serum immunoglobulin levels (and complement subfactors). Also there were insignificant differences between epileptic patients before and ٣ months after therapy with valproate . Conclusion: valproate as an anticonvulsant have no influence on serum immunoglobulin (IgG, IgA, IgM) and complement subfactors (C٣, C٤) after ٣ months of therapy.